Private and Public English Teachers' Readiness in Implementing 21st Century Skills at Primary Schools - Pujana, Dw Gede Partiwa (International Journal of Language and Literature, 2022)
The teachers in this era have an essential role in implementing 21st-century skills to the students. The teachers need to be ready and understand the skills 21st century. Thus, this study intends to investigate the primary school teachers' readiness in implementing 21st-century skills, specifically in teaching English. The readiness of teachers can assess from their lesson plan, teaching and learning process and assessment. The sequential embedded mixed-method used as the method of this study. In collecting the data, questionnaires and observation were used to obtain the data and supported by interviews. The data showed that the result of the questionnaires related to the teachers' readiness in implementing the 21st-century skills was high. However, the observation result showed low insertion of the skills of the 21st century conducted by the teachers. Those indicate the implementation of 21st-century skills were not inserted fully by the teachers. Moreover, the teachers have to understand the 21st-century skills as essential skills to survive in the 21st-century era,